2018
DOI: 10.18203/2394-6040.ijcmph20183980
|View full text |Cite
|
Sign up to set email alerts
|

Study on knowledge about gestational diabetes mellitus and its risk factors among antenatal mothers attending care, urban Chidambaram

Abstract: Background: Gestational diabetes mellitus (GDM) is a growing epidemiological problem. GDM is defined as the glucose intolerance during pregnancy. Treatment of GDM is important to avoid maternal and fetal complications. The objectives of this study was to assess the knowledge about GDM among antenatal mothers and to find out the association between knowledge and demographic factors.Methods: A descriptive cross sectional study was done among 191 antenatal mothers in Maternity Health Centre and Government Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 5 publications
(6 reference statements)
2
9
0
Order By: Relevance
“…Lack of knowledge on anemia could be one reason for the high prevalence of anemia in Bangladesh. Our finding of poor knowledge of GDM is aligned with studies conducted in Bangladesh and other low-and-middle-income countries [74,75]. Compared to diabetes and anemia, knowledge of hypertension was better, especially among postpartum women, presumably because some had developed hypertension during their pregnancy.…”
Section: Discussionsupporting
confidence: 84%
“…Lack of knowledge on anemia could be one reason for the high prevalence of anemia in Bangladesh. Our finding of poor knowledge of GDM is aligned with studies conducted in Bangladesh and other low-and-middle-income countries [74,75]. Compared to diabetes and anemia, knowledge of hypertension was better, especially among postpartum women, presumably because some had developed hypertension during their pregnancy.…”
Section: Discussionsupporting
confidence: 84%
“…The inadequate knowledge of anemia demonstrated by the participants in our study needs to be addressed in this context. Our nding of poor knowledge of GDM is aligned with studies conducted in Bangladesh and other low-and-middle-income countries [17,67]. has been found to be more effective than one-way communication in other settings; as a result, this option was not discussed with women [69].…”
Section: Name Of Health Facilitysupporting
confidence: 72%
“…Complications, such as anemia [16], gestational diabetes mellitus (GDM) and hypertensive disorders in pregnancy [9] are common in South East Asia including Bangladesh [17][18][19]. Therefore, screening for these three conditions during pregnancy is essential, especially given that there are few symptoms at the early stages of these illnesses.…”
mentioning
confidence: 99%
“…Bhowmik et al, Balaji et al and Lakshmi et al reported similar findings. In these studies, participants with higher educational status were found to have a significantly higher mean knowledge score than their counterparts [ 10 , 13 , 24 ]. This could be because education has a strong impact on health literacy; that is, pregnant women with higher education status are able to read health posters, get information from health-related articles and literature and have better understanding of the health information given to them by the health personnel during antenatal care.…”
Section: Discussionmentioning
confidence: 99%